Two studies on news diffusion of the missing Malaysian plane / Syed Arabi Idid. - Idid, Syed Arabi (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
Methodology is one neglected area in studying news diffusion. Studies on news diffusion require speed in the conduct of their research for fear of memory loss and poor recollection on the date and time of occurrence of the significant event. Diffusion of news is about tracing the flow of news of a significant event from the time of news announcement in the media to the audience and from them to other members in society. Several studies have been made on the flow and rate of flow in the transmission of significant events, given different incidents, different time and different places but the discussion on methodology has been minimal. This study focuses on the problem of methodology in conducting news diffusion in two different areas related to a significant event, namely the airline tragedy of the Malaysia Airlines Flight MH370 that went missing in March 2014. The two studies were conducted to know whether there would be differences in knowing by time and place. One study was made in Kajang, in the suburb of Kuala Lumpur two weeks after the event. A second study was conducted nation-wide two months later. The study found no marked differences in time and date of recall or in the nature of news transmission, suggesting that audience members could recall time and date of the significant event. One possible reason could be the news of the missing plane continued to be a news item even two months after it was found missing and this might have affected respondents recall of the time and date.